Outcomes of decompression for lumbar spinal canal stenosis based upon preoperative radiographic severity - Patel Nilesh M; Weiner Bradley K; Walker Matthew A (Journal of Orthopaedic Surgery and Research, 2007)
Abstract Background The relationship between severity of preoperative radiographic findings and surgical outcomes following decompression for lumbar degenerative spinal canal stenosis is unclear. Our aim in this paper was to gain insight into this relationship. We determined pre-operative radiographic severity on MRI scans using strict methodological controls and correlated such severity with post-operative outcomes using prospectively collected data. Methods Twenty-seven consecutive patients undergoing decompression for isolated degenerative spinal canal stenosis at L4-L5 were included. We measured cross-sectional area on MRI using the technique of Hamanishi. We categorized the severity of stenosis using Laurencin and Lipson's 'Stenosis Ratio'. We determined pre-operative status (prospectively) and post-operative outcomes using Weiner and Fraser's 'Neurogenic Claudication Outcome Score'. We determined patient satisfaction using standardized questionnaires. Each of these is a validated measure. Formal statistical evaluation was undertaken. Results No patients (0 of 14) with a greater than 50% reduction in cross-sectional area on pre-operative MRI had unsatisfactory outcomes. In contrast, outcomes for patients with less than or equal to 50% reduction in cross-sectional area had unsatifactory outcomes in 6 of 13 cases, with all but one negative outcome having a cross-sectional area reduction between 32% and 47%. Conclusion The findings suggest that there appears to be a relationship between severity of stenosis and outcomes of decompressive surgery such that patients with a greater than 50% reduction in cross sectional area are more likely to have a successful outcome.